Reputation
Next privilege 50 Rep.
Comment everywhere
Badges
2
Newest
 Editor
Impact
~61 people reached

  • 0 posts edited
  • 0 helpful flags
  • 0 votes cast
Nov
19
comment $(y^{2} − 1) + 2(x − y(1 + y)^{2})y' = 0$ What method should I use to solve this ODE?
Wow, thx. I never know this. Where can I find out the derivation of this formula ?
Nov
19
awarded  Editor
Nov
19
comment $(y^{2} − 1) + 2(x − y(1 + y)^{2})y' = 0$ What method should I use to solve this ODE?
Ok..how to figure out this integrating factor then ? making $y^2-1 = M$ the coefficient of $y'$ is $N$ $M_y = 2y,N_x = 2$, Then ?
Nov
19
revised $(y^{2} − 1) + 2(x − y(1 + y)^{2})y' = 0$ What method should I use to solve this ODE?
added 128 characters in body
Nov
19
awarded  Student
Nov
19
asked $(y^{2} − 1) + 2(x − y(1 + y)^{2})y' = 0$ What method should I use to solve this ODE?